2003
DOI: 10.7326/0003-4819-138-1-200301070-00007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Renin–Angiotensin System and Abdominal Adiposity in Men: The Olivetti Prospective Heart Study

Abstract: The ACE I/D polymorphism was a significant predictor of overweight and abdominal adiposity in men. DD homozygosity was associated with larger increases in body weight and blood pressure in aging persons, as well as with higher incidence of overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
118
5
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 44 publications
7
118
5
1
Order By: Relevance
“…7 In the present study, the effects of the ACE I/D polymorphism on adiposity indices were investigated in a population of toddlers and preschool children. The D-allele was significantly associated with higher scores for three adiposity-related phenotypes (BMI, waist and arm circumference) in girls aged 4-6 years (Table 2), a finding in agreement with previous studies in teenagers 18 and adults, 26,27 where DD individuals showed increased adiposity compared to II and ID genotypes. In boys 3-4 years old, homozygotes for the D-allele were also significantly associated with higher suprailiac skinfold (Table 1), again in agreement with a previous report showing increased adiposity in Italian men of the DD genotype.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…7 In the present study, the effects of the ACE I/D polymorphism on adiposity indices were investigated in a population of toddlers and preschool children. The D-allele was significantly associated with higher scores for three adiposity-related phenotypes (BMI, waist and arm circumference) in girls aged 4-6 years (Table 2), a finding in agreement with previous studies in teenagers 18 and adults, 26,27 where DD individuals showed increased adiposity compared to II and ID genotypes. In boys 3-4 years old, homozygotes for the D-allele were also significantly associated with higher suprailiac skinfold (Table 1), again in agreement with a previous report showing increased adiposity in Italian men of the DD genotype.…”
Section: Discussionsupporting
confidence: 92%
“…girls aged 4-6 years in the present study) may interact with the ACE I/D polymorphism and in doing so influence body fat accumulation in a similar manner as previously reported in Greek teenage girls. 18 Although the present study provides further support for the ACE I/D polymorphism being a good candidate gene for human obesity, 18,26,27 the precise mechanism by which ACE may produce this effect remains unclear. The primary role of ACE is to convert angiotensin I into angiotensin II (a potent vasoconstrictor).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We used a cohort of young male subjects (n ¼ 395) followed up for 28 years from the Olivetti Heart Study, a survey of cardiovascular risk factors carried out in Southern Italy. 11 At baseline (1975) and subsequent follow-up visits (1987, 1994-1995, and 2002-2004), each participant underwent anthropometry and BP measurements, and a venous blood sample was drawn. Personal and familiar medical history was collected in the interview.…”
mentioning
confidence: 99%